Renin-Angiotensin-Aldosterone System Inhibitors, Statins, and Beta-Blockers in Diabetic Patients With Critical Limb Ischemia and Foot Lesions. (20th May 2022) - Cimaglia, Paolo; Bernucci, Davide; Cardelli, Laura Sofia; Carone, Anna; Scavone, Giuseppe; Manfrini, Marco; Censi, Stefano; Calvi, Simone; Ferrari, Roberto; Campo, Gianluca; Dalla Paola, Luca
Medical therapy for secondary prevention is known to be under-used in patients with peripheral artery disease (PAD). Few data are available on the subgroup with critical limb ischemia (CLI). Prescription of cardiovascular preventive therapies was recorded at discharge in a large, prospective cohort of patients admitted for treatment of CLI and foot lesions, stratified for coronary artery disease (CAD) diagnosis. All patients were followed up for at least 1 year. The primary endpoint was major adverse cardiovascular events (MACE). 618 patients were observed for a median follow-up of 981 days. Renin-angiotensin-aldosterone system (RAAS) inhibitors, statins, beta-blockers, and antithrombotic drugs were prescribed in 52%, 80%, 51%, and 99% of patients, respectively. However, only 43% of patients received optimal medical therapy (OMT), defined as the combination of RAAS inhibitor plus statin plus at least one antithrombotic drug. It was observed that the prescription of OMT was not affected by the presence of a CAD diagnosis. On the other hand, it was noticed that the renal function affected the prescription of OMT. OMT was independently associated with MACE (HR 0.688, 95%CI 0.475-0.995, P = .047) and, after propensity matching, also with all-cause mortality (HR 0.626, 95%CI 0.409-0.958, P = .031). Beta-blockers prescription was not associated with any outcome. In conclusion, patients with critical limb ischemia are under-treated with cardiovascular preventive therapies, irrespective of a CAD diagnosis. This has consequences on their prognosis.